Spontaneous Breathing Trial with Pressure Support Ventilation and Outcome of Extubation (Journal of the Bangladesh Society of Anaesthesiologists, 2022)
Background: Failure to wean causes prolonged ICU stay, increases complications associated withmechanical ventilation and increases morbidity and mortality. Spontaneous breathing trial (SBT) isthe final step of weaning before extubation.Objective: To observe the efficacy of pressure support ventilation (PSV)method of spontaneousbreathing trial(SBT) for successful extubation.Methods: This prospective observational study was carried out in the Department of Anesthesia,Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College & Hospital from January2015 to December 2016. A total of 116 patients on ventilator who were ready for spontaneous breathingtrial, were enrolled in this study. Patients were divided randomly into two groups. Among them, 58patients underwent SBT using PSV and remaining 58 patients underwent SBT using T-piece.Result: Mean duration of SBT among SBT failure patients was higher in PSV group than T-piecegroup (107.1±16.0 vs 85.0±25.0). Among the patients successfully completing SBT, re-intubation wasrequired in 15.2% cases and 17.6% cases in T-piece and PSV group respectively. 67.2% patients inT-piece group and 72.4% patients in PSV group were successfully extubated, extubation failure occurredin 12.1% and 15.5% cases in T-piece and PSV group respectively and SBT failure occurred in 20.7% and12.1% cases in T-piece and PSV groups respectively.Conclusion: Tolerance of the SBT and successful extubation were high in both groups but relativelyhigher in PSV group. Reintubation rate was almost same in both groups. None of these findings werestatistically significant.JBSA 2022; 35 (1) : 37-45